Credit Access as a Nexus of Profitability: The Resilience of Smallholder Broiler Contract Farming - Lisa Dwi Lestari; Widyastutik; Muladno (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: The unequal access to resources in the broiler industry hinders smallholders from competing effectively. To address this issue, farmers are being urged to engage in contract farming as a means to boost profits and improve access to credit. However, despite efforts to facilitate credit disbursement, empirical studies indicate that poultry farm loans are underutilized. These studies also demonstrate that not all farmers consistently benefit from increased profits and improved credit access.Purpose: This research was conducted to answer the nexus between credit access and profitability. Furthermore, this study reviews the problems and the role of contract farming on farmers' credit access. Design/methodology/approach: The investigation encompassed an analysis of 51 broiler plasma farmers affiliated with an integrator company in West Java. To elucidate the research objectives, a profitability analysis was conducted, employing both gross margin assessment and the Ordinary Least Squares (OLS) method within a multiple regression framework. Findings/Result: The research findings elucidate that profitability among farmers is not guaranteed, with operational losses frequently attributed to negligence, adverse climatic conditions, and disease outbreaks. Consequently, some farmers must seek financial credit to sustain working capital and facilitate business expansion. Specifically, investment credit is allocated for the enhancement or construction of cages and equipment, whereas working capital credit aims to expedite the turnover of operational expenses. An Ordinary Least Squares (OLS) regression analysis revealed significant determinants of profit, including access to credit, flock size, ownership of cages and land, employment of hired labor, and the farmer's age. Parameter estimation further delineated that, ceteris paribus, farmers who engaged in credit utilization reported substantially higher profits, amounting to IDR11,949 million more than their counterparts who did not access credit. It is noteworthy that credit application processes that bypass integrator companies necessitate sufficient collateral to secure the loans, limiting access to bank credit strictly to farmers who possess adequate collateral. According to the survey data, a mere 13,7%. The role of contract farming in mitigating the asymmetry of information regarding credit access remains suboptimal.Conclusion: The results rejected the hypothesis that credit access does not affect profit. However, farmers' utilization of credit access is relatively small and the distribution of credit access among plasma farmers engaged in contract farming is characterized by inequity.Originality/value (State of the art): This study addressed the vital role of credit access toward farmers’ profitability. This study combined Ricardo's theory and principal agency theory, applied to contract farming in the broiler industry. This sharpened the importance of the integrator company's role in providing capital and financing facilities to farmers based on the principle of risk sharing, thereby reducing the company’s risk. Keywords: contract farming, gross margin, credit access, broiler, smallholder